Effect of skeletal muscle demand on cardiovascular function - Harms, C. A. (Medicine & Science in Sports & Exercise, 2000)
Cardiac output is directed primarily to skeletal muscle during exercise. Recent investigations have examined how different groups of skeletal muscle compete for the cardiac output during exercise. To date, there is a lack of consistent findings on a blood flow steal effect of arm versus leg exercise, although the majority of data suggest that leg blood flow is not compromised when arm exercise is added to leg exercise. A recent set of experiments have demonstrated that respiratory muscles compete favorably for blood flow with the legs during maximal exercise. Decreased work of breathing leads to: 1) a decrease in cardiac output, due primarily to reduced stroke volume; and 2) increased leg blood flow and leg vascular conductance. An increased work of breathing leads to the converse. Exercise performance may also be affected by the work of breathing during heavy exercise due to redistribution of blood flow between the chest wall and the locomotor muscles. It appears that in contrast to arm exercise, respiratory muscles demand a significant portion of the cardiac output during maximal exercise, and the work of breathing normally experienced during heavy exercise compromises leg blood flow.